On Method Concept for Safety Culture Assessment with Application of Inductive Learning Algorithms - Begun, V.V.; Lytvynov, V.V.; Begun, S.V. (Управляющие системы и машины, 2014)
Предложен новый универсальный алгоритм расчета уровня культуры безопасности, применяемый для анализа состояния безопасности потенциально опасного объекта. Использован метод группового учета аргументов. Описана процедура расчета весовых коэффициентов и соответствующая процедура нормировки для адекватного учета вклада от разных индикаторов в интегральный показатель уровня культуры безопасности. The new universal algorithm for safety culture level assessment is proposed, it is applicable for the safety analysis of any kind of the dangerous object. The Group Method of Data Handling is used. Weighting coefficients calculation procedure with corresponding normalization procedure are proposed for adequate account of the different safety indicators contribution to the integral safety culture level index. Запропоновано новий універсальний алгоритм розрахунку рівня культури безпеки, застосовний до аналізу стану безпеки потенційно небезпечного об’єкта. Використано метод групового врахування аргументів. Описано процедуру розрахунку вагових коефіцієнтів та відповідну процедуру нормування для адекватного врахування внеску від різних індикаторів у інтегральний показник рівня культури безпеки.